Analisis Pengaruh Brand Image, Brand Awareness dan Brand Trust terhadap Purchase Decision Smartphone Merek Oppo di Kecamatan Majalaya - Muhammad Farhan Januar; Dedy Ansari Harahap, Nindya Saraswati; Nindya Saraswati (Bandung Conference Series: Business and Management, 2024)
Abstract. The need for smartphones in Indonesia is increasing due to the increase in the use value of smartphones, this has made the competition in the smartphone industry even tighter. Facing this competition, companies need to know the factors that cause consumers to choose a product. The purpose of this study was to analyze the influence of brand image, brand awareness and brand trust on purchase decisions for Oppo brand smartphones in Majalaya sub-district. This type of research is included in descriptive and verification research with quantitative methods. This research was conducted by distributing questionnaires to 160 respondents. The sampling technique used is non-probability sampling. The analytical method used is multiple linear regression analysis with the help of SPSS 25 software, hypothesis testing using the T test and F test. The results of the study show that brand image partially has no significant effect on purchase decisions. Brand awareness partially has a significant effect on purchase decision. Brand trust partially has a significant effect on purchase decision. As well as brand image, brand awareness and brand trust simultaneously have a significant effect on the purchase decision of the Oppo brand smartphone in Majalaya sub-district. Abstrak. Kebutuhan akan smartphone di Indonesia meningkat karena peningkatan nilai guna smartphone, hal ini membuat persaingan industri smartphone semakin ketat. Menghadapi persaingan ini, perusahaan perlu mengetahui faktor penyebab konsumen memilih suatu produk. Tujuan penelitian ini adalah untuk menganalisis pengaruh brand image, brand awareness dan brand trust terhadap purchase decision smartphone merek Oppo di kecamatan Majalaya. Jenis penelitian ini termasuk dalam penelitian deskriptif dan verifikatif dengan metode kuantitatif. Penelitian ini dilakukan dengan menyebarkan kuesioner kepada 160 responden. Teknik sampling yang digunakan adalah non probability sampling. Metode analisis yang digunakan adalah analisis regresi linear berganda dengan bantuan software SPSS 25, uji hipotesis menggunakan Uji T dan Uji F. Hasil penelitian menunjukan bahwa brand image secara parsial tidak berpengaruh signifikan terhadap purchase decision. Brand awareness secara parsial berpengaruh signifikan terhadap purchase decision. Brand trust secara parsial berpengaruh signifikan terhadap purchase decision. Serta brand image, brand awareness dan brand trust secara simultan berpengaruh signifikan terhadap purchase decision smartphone merek Oppo di kecamatan Majalaya.